Stable carbon fractionation in size-segregated aerosol particles produced by controlled biomass burning. (January 2015) - Garbaras, A.; Masalaite, A.; Garbariene, I.; Ceburnis, D.; Krugly, E.; Remeikis, V.; Puida, E.; Kvietkus, K.; Martuzevicius, D.
Abstract: Six different biomass fuel types (wood pellets, sunflower stalk pellets, straw pellets, buckwheat shells, mixed biomass waste pellets, and grain screenings) and wastewater sludge pellets were burned under controlled conditions to determine the effect of the biomass type on the emitted particulate matter mass and stable carbon isotope composition of bulk and size-segregated particles. Aerosol particles were sampled using the total suspended particle (TSP) sampler and a micro-orifice uniform deposit impactor (MOUDI). The results demonstrated that particle emissions were dominated by the submicron particles (size <1 µm) in all biomass types. However, significant differences in emissions of submicron particles and their dominant sizes were found between different biomass fuels. The isotopic fractionation between aerosol particles and original biomass material varied from −0.94±0.23‰ to 1.12±0.16‰. The largest negative fractionation −0.94±0.23‰ was obtained for the wood pellet fuel type while the largest positive isotopic fractionation (1.12±0.16‰) was observed during the grain screenings combustion. The carbon isotope composition of MOUDI samples compared very well with the isotope composition of TSP samples indicating consistency of the results. The measurements of the stable carbon isotope ratio in size-segregated aerosol particles suggested that combustion processes could strongly affect isotopic fractionation in aerosol particles of different sizes thereby potentially affecting an interpretation of ambient atmospheric observations. Highlights: Different biomass fuel types were investigated during controlled burning conditions. Stable carbon isotopes were analyzed in size-segregated aerosol particles and TSP. Stable carbon isotope fractionation (Δ 13 C) between aerosol particles and fuel depended on combustion conditions. For the various biomass fuel types Δ 13 C was different in separate aerosol particle sizes.